2015
DOI: 10.1002/dvdy.24232
|View full text |Cite
|
Sign up to set email alerts
|

Input overload: Contributions of retinoic acid signaling feedback mechanisms to heart development and teratogenesis

Abstract: Appropriate levels of retinoic acid (RA) signaling are critical for normal heart development in vertebrates. A fascinating property of RA signaling is the thoroughness by which positive and negative feedback are employed to promote proper embryonic RA levels. In the present short review, we first cover the advancement of hypotheses regarding the impact of RA signaling on cardiac specification. We then discuss our current understanding of RA signaling feedback mechanisms and the implications of recent studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 135 publications
(254 reference statements)
0
51
0
Order By: Relevance
“…Because RA production is maintained in homeostatic balance via feedback regulation (D’Aniello and Waxman, 2015; Sandell et al, 2012), and because of the reversible nature of the Retinol/Retinal conversion reaction, supplementation with atRAL at these dosage levels does not markedly disturb normal RA signaling in wild type embryos (Fig. 2 A–C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because RA production is maintained in homeostatic balance via feedback regulation (D’Aniello and Waxman, 2015; Sandell et al, 2012), and because of the reversible nature of the Retinol/Retinal conversion reaction, supplementation with atRAL at these dosage levels does not markedly disturb normal RA signaling in wild type embryos (Fig. 2 A–C).…”
Section: Resultsmentioning
confidence: 99%
“…6 C and 3 E), we do not know if the RA is present the cultured glands accurately reflects the RA signaling pattern that occurs in vivo. In vivo , disturbances of RA signaling levels are buffered by feedback regulation of RA production, RA signaling, and RA degradation, and can yield paradoxical consequences in RA regulation (D’Aniello et al, 2013; D’Aniello and Waxman, 2015; Lee et al, 2012; Sandell et al, 2012). Thus, it is possible that cultured glands, lacking the Vitamin A precursor normally available in circulating serum, experience feedback regulatory changes in RA homeostasis relative to glands in vivo , possibly increasing transcription of RAR receptors or decreasing transcription of RA degrading enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…This is attested foremost by the fact that Cyp26 enzymes were first identified in studies investigating genes upregulated upon RA exposure in mouse embryonic stem (ES) cells and zebrafish embryos (Ray et al, ; White et al, ). The administration of exogenous RA to developing embryos was shown to upregulate the expression and spatial domains of Cyp26 enzymes in Xenopus , zebrafish, and Ciona , often with a concomitant downregulation of RA synthesis enzymes (D'Aniello & Waxman, ; Dobbs‐McAuliffe, Zhao, & Linney, ; Ishibashi et al, ; Tanibe et al, ). Indeed, studies in zebrafish embryos demonstrated that the ability of RA to induce the expression of Cyp26 enzymes is the mechanism behind prolonged loss of RA after a teratogenic insult.…”
Section: Cyp26‐mediated Ra Gradients Formation and Regulationmentioning
confidence: 99%
“…Conversely, genes involved in RA catabolism are expressed in regions of the embryo where RA signaling is absent [167,168,169]. Many of the vitamin A metabolic, or catabolic genes are controlled by positive and negative feedback from RA signaling (reviewed in [170]). Genes that are transcriptionally regulated by feedback from RA include those involved in vitamin A metabolism and RA production [104,106,133,134,164].…”
Section: Tissue-specific Gene Expression and Feedback Regulationmentioning
confidence: 99%